Insulin resistance in uremia. Characterization of lipid metabolism in freshly isolated and primary cultures of hepatocytes from chronic uremic rats. - Caro, J F (1983)
We have studied the mechanism(s) of hyperlipidemia and liver insulin sensitivity in a rat model of severe chronic uremia (U). Basal lipid synthesis was decreased in freshly isolated hepatocytes from U when compared with sham-operated ad lib.-fed controls (alfC). Basal lipid synthesis in pair-fed controls (pfC) was in between U and alfC. Similarly, the activity of liver acetyl CoA carboxylase, fatty acid synthetase, citrate cleavage enzyme, malate dehydrogenase, and glucose-6-phosphate dehydrogenase was diminished in U. Muscle and adipose tissue lipoprotein lipase was also decreased. Insulin stimulated lipid synthesis in freshly isolated hepatocytes from alfC. Hepatocytes from U and pfC were resistant to this effect of insulin. To ascertain if the insulin resistance in U was due to starvation (chow intake 50% of alfC) or to uremia itself, the U and pfC were intragastrically fed an isocaloric diet via a Holter pump the last week of the experimental period. Hepatocytes from orally fed U and pfC were also cultured for 24 h in serum-free medium. While freshly isolated and cultured U hepatocytes remained insulin resistant, those from pfC normalized, in vivo and in vitro, when they were provided with enough nutrients. Conclusions: (a) Hyperlipidemia in uremia is not due to increased synthesis, but to defect(s) in clearance. (b) Insulin does not stimulate lipid synthesis in uremia. This finding, along with our recent demonstration that insulin binding and internalization are not decreased in the uremic liver, suggests that a post-binding defect(s) in the liver plays an important role in the mechanism(s) of insulin resistance in uremia. (c) Cultured hepatocytes from uremic rats remain insulin resistant. This quality renders these cells useful in studying the postinsulin binding events responsible for the insulin-resistant state in the absence of complicating hormonal and substrate changes that occur in vivo.